Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.15241/sh.4.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Career-Development Needs of Student Veterans: A Proposal for Career Interventions

Abstract: The American Community Survey (ACS; U.S. Census Bureau, 2011) estimated that 21.5 million veterans live in the United States. A reported 1.6 million veterans served in the Gulf War operations that began post-9/11 in 2001 (U.S. Census Bureau, 2011). Gulf War post-9/11 veterans served mainly in Iraq and Afghanistan, in operations including but not limited to Operations Enduring Freedom (OEF), Iraqi Freedom (OIF), and New Dawn (OND) (M. E. Otey, personal communication, October 23, 2012). Holder (2007) estimated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Research has emphasized the need to investigate student veterans’ career transitions. For example, in a study of 317 veterans, most participants indicated they wanted to learn how to transfer skills they learned in the military to the workplace (Hayden, Ledwith, Dong, & Buzzetta, 2014). In a qualitative study with 14 veterans, Krieshok, Hastings, Ebberwein, Wettersten, and Owen (1999) found that veterans who transitioned to civilian life after deployments encountered several challenges regarding their vocational identities.…”
Section: Career Transitionsmentioning
confidence: 99%
“…Research has emphasized the need to investigate student veterans’ career transitions. For example, in a study of 317 veterans, most participants indicated they wanted to learn how to transfer skills they learned in the military to the workplace (Hayden, Ledwith, Dong, & Buzzetta, 2014). In a qualitative study with 14 veterans, Krieshok, Hastings, Ebberwein, Wettersten, and Owen (1999) found that veterans who transitioned to civilian life after deployments encountered several challenges regarding their vocational identities.…”
Section: Career Transitionsmentioning
confidence: 99%
“…This feature is "above and beyond" the usual listing of the military service on an individual's resume only. Research gleaned from survey respondents showed that the number one perceived career development need for an institution to remedy was, "Transferring skills gained in the military to the workplace" (Hayden et al, 2014). Building upon this study's results and discussion, it is important for higher education organizations to provide applicable, well thought out, inclusive, veteran career programming and services to meet the career goals of participating military connected students as they transition from their military work experience through higher education toward the civilian workplace.…”
Section: Resultsmentioning
confidence: 99%
“…In an empirical study, authors indicated, "Survey respondents, along with group or workshop participants, could be recruited to provide feedback as part of a career-development focus group, further informing research and application for student veterans' career concerns" (Hayden et al, 2014), which aligns with recommendations six and seven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,19 Researchers have identified the challenges experienced by student veterans in translating their military experience to specific civilian career paths. 19,20 As Hayden and Scholl contend, career development for military veterans needs to more effectively integrate experiences, job skills, and personal characteristics gained through military experiences itself. 21 Considering the unique career pathways of veterans, there is limited research on how student veterans decide to major in a particular field, to make career choices, and whether student veterans' military experience shapes these decisions.…”
Section: Career Intentions and Decision Making Of Student Veteransmentioning
confidence: 99%